A CONSTITUTIONAL PERSPECTIVE ON THE VALIDITY OF THE KWAZULU-NATAL POUNDS LEGISLATION Zondi v Member of the Executive Council CCT 73/03 - Nic Olivier; Annabelle Reddy (Obiter, 2022)
The Constitution of the Republic of South African, 1996 (“the Constitution”) is a tool seen to be the mechanism for the eradication of the injustices of the past faced by many South Africans. This includes, amongst others, the denial of access to courts that would enable ordinary citizens to protect their rights. The recent decision in Zondi v Member of the Executive Council (CCT 73/03) highlights core elements of constitutional and administrative justice in that the supremacy of the fundamental rights enshrined in the Constitution was upheld while simultaneously striking down conflicting provisions of the contentious Natal Pound Ordinance 32 of 1947 (“Ordinance”). This Ordinance was assigned to the KwaZulu-Natal Provincial Government in terms of Proclamation 107 of 1994. The KwaZulu-Natal Executive transferred the administration of the 1947 Ordinance from the MEC for Agriculture to the MEC for Local Government (KZN Proclamation 5 of 13 June 2003).